Development of artificial one-part geopolymer lightweight aggregates by crushing technique. (15th September 2021) - Xu, Ling-Yu; Qian, Lan-Ping; Huang, Bo-Tao; Dai, Jian-Guo
Abstract: The production method of geopolymer lightweight aggregates (GLAs) is explored in this study through crushing technique, which has a good prospect for massive industrial production. Geopolymer cubes with the dimension of 100 mm × 100 mm × 100 mm were firstly produced using one-part geopolymer technology and then crushed into coarse aggregates with angular shapes. Coal fly ash (FA), ground granulated blast-furnace slag (GGBS) and anhydrous sodium metasilicate particles in industrial grades were utilized for the one-part geopolymer in this study. Results showed that the produced GLAs with different mixes were all lightweight with a loose bulk density below 800 kg/m 3 and an apparent density of 1450–1750 kg/m 3 . The produced GLAs were further used as coarse aggregates to produce geopolymer aggregate concrete (GAC). It was found that for GLAs, the increase in alkalinity and the addition of GGBS resulted in a higher one-day compressive strength, which would make better aggregate shapes, but need higher crushing energy and might cause initial damage to the aggregates. The highest cylinder compressive strength was obtained in GLAs with pure fly ash as the precursor and the activator to precursor ratio of 14%. However, the highest compressive strength of geopolymer aggregate concrete (GAC) was obtained using GLAs with 20% GGBS addition and the activator to precursor ratio of 12% although the cylinder compressive strength of this type of aggregates was not the highest. It was found that the addition of GGBS in GLAs resulted in stronger aggregate-matrix interface in GAC. Finally, the embodied carbon and material cost of GLAs were analyzed. The findings in this study are useful for future production and application of GLAs in concrete industry. Highlights: Geopolymer lightweight aggregates (GLAs) were produced using one-part geopolymer technology and crushing method. Geopolymer aggregate concrete (GAC) was produced using GLAs. The effects of geopolymer mix proportions on the GLAs and lightweight GAC were investigated. The GLA-mortar matrix interface in GAC was characterized in details. A 4-dimensional representation was introduced for assessing the overall performance of GLAs.